Influência do exercício aeróbico sobre o perfil de expressão de microRNAs e RNAs mensageiros na formação hipocampal de ratos adultos - Fernandes, Jansen [UNIFESP] (2017)
The scientific literature has extensively documented the beneficial effects of physical exercise on brain function. Physical exercise has the ability to improve the cognitive function, decrease age-related memory loss, delay the onset of neurodegenerative diseases, facilitate recovery after brain injury and improve depressive symptoms. MicroRNAs (miRNAs) are small, non-coding RNAs of approximately 23 nucleotides that act as potent silencers of gene expression by inducing translational repression or degradation of target mRNA. miRNAs regulate the expression of genes involved in several biological processes, such as cell cycle, apoptosis, and cell differentiation. These molecules are abundantly present in the adult brain and have a spatiotemporal expression pattern. The neurobiological role of these molecules in processes such as brain development, aging, injury, cognition and neurological disorders, has received more attention only in recent years. To verify whether physical exercise can modulate the activity of miRNA-mRNA network in the brain, differential expression analysis was performed in the hippocampus of control (CTL) and exercise-trained (Ex) rats euthanized 2 (Ex2) and 26 (Ex26) hours after the last exercise session of 4 weeks exercise program. Using Illumina next-generation sequencing (NGS) for miRNA profile, we identified 4 miRNAs significantly altered in the hippocampus of Ex2 group when compared to CTL animals. Among these miRNAs, the expression of miR-129-1-3p, miR-144-5p and miR10b-5p were significantly upregulated whereas the miR-708-5p was significantly downregulated. Additionally, it was found 54 differentially expressed genes in the hippocampus of Ex2 animals when compared to CTL group. Bioinformatic analysis showed an inverse correlation between 3 miRNAs and 6 target genes. While the miRNAs miR-129-1-3p and miR-144-5p were inversely correlated to the Igfbp5 and Itm2a, respectivelly, the miR-708-5p presented an inverse correlation with Cdkn1a, Per2, Rt1a2. No difference was observed in the Ex26 group. Altogether, these data raise the possibility that physical exercise can affect brain function through modulation of miRNA-mRNA regulatory network.